Terahertz Generation in Laser-Induced Gas-Plasmas - Edwardsson, Per; Hallborn, Hanna; Strandberg, Erik (My University, 2018)
In this thesis the THz generation mechanism for a two-color laser pulse induced gas plasma is investigated. A fluid model for the laser-plasma interaction is presented and discussed. The model is discretised and implemented in a computational code, and the scheme is tested and compared to published results of a similar model. The simulations are used to show the impact of different parameters of the laserplasma interaction on THz generation. The different trends that are found are then discussed and compared to the theory of THz generation. Keywords: Plasma, Terahertz, Laser, Laser-Plasma-Interaction, Simulation, Maxwell, Partial Differential Equations.
Keywords: Fysik; Physical Sciences